Considerations on Safety Parameters for Flames of Cold and Cryogenic Gases - Sven Eckart; Ernesto Salzano; Loreto Pizzuti; Hartmut Krause; Gianmaria Pio (Chemical Engineering Transactions)
The continuous development of alternative and optimized solutions for a convenient and sustainable utilization of cryogenic conditions has recently involved several industrial sectors, including fuel transportation. The availability of large quantities of flammable and hazardous materials stored under extremely low temperatures requires specific evaluations on the safety of these innovative solutions to guarantee a robust spread worldwide as well as to provide sufficient information for proper protocols and regulations. Evaluating the laminar burning velocity represents an essential step toward the achievement of these targets. To this scope, a comparative analysis of the existing techniques for the experimental characterization of low initial temperature reactive systems in terms of laminar burning velocity is presented in this work. Among the others, the heat flux burner was identified as a promising solution for the experimental quantification of the laminar burning velocity at low temperatures, although the current layout does not allow for the investigation of these conditions. Therefore, possible modifications were proposed to adapt a heat flux burner for these extreme conditions, ensuring precise and reliable measurements. In addition, a numerical analysis assessing the effects of the initial temperature on the flammability limits of cryogenic fluids was presented. The collected data can be also intended as indications for further refining the design of the existing burners, allowing for accurate experimental determination of laminar burning velocity at low initial temperature and, thus, validation of kinetic mechanisms and utilization of advanced models for consequence analyses.